Case Report: Disease progression of renal cell carcinoma containing a novel putative pathogenic KAT6A::NRG1 fusion on Ipilimumab- Nivolumab immunotherapy. A case study and review of the literature - Dawood, Almas; MacMahon, Suzanne; Dang, My-Anh Tran; Tran, Maxine G. B.; Bex, Axel; Boleti, Ekaterini; Sheikh, Soha El (Frontiers in Oncology, 2023)
Renal cell carcinoma still carries a poor prognosis despite therapeutic advancements. Detection of genetic mutations is vital in improving our understanding of this disease as well as potential role in targeted therapy. Here we present a case of a 49 year old man with an aggressive renal cell carcinoma bearing a novel pathogenic KAT6Aa::NRG1 fusion. We will explore the clinical presentation, histological and molecular diagnostics, treatment and disease progression. We will discuss the relevance of this unique fusion and comparisons with cancer cases with similar genetic mutations. Further research is warranted for such cases, in order to facilitate better targeted treatments.